Immune function and exercise - Gleeson, M. (European Journal of Sport Science, 2004)
This review will examine the effects of exercise and training on immune func-tion and will discuss the methodological problems that limit the interpretation of many exercise immunology studies. Acute bouts of exercise cause a tempo-rary depression of various aspects of immune function, such as neutrophil oxidative burst, lymphocyte proliferation, monocyte MHC class II expression, and natural killer cell cytotoxic activity, that will usually last for approximately three to 24 hours after exercise, depending on the intensity and duration of the exercise bout. Post-exercise immune function depression is most pronounced when the exercise is continuous, prolonged (<1.5 hours), of moderate to high intensity (55-75% VO2max), and performed without food intake. Periods of intensified training that result in overreaching have been shown to chronically depress immune function - i.e., immune cell functions measured at rest are still depressed 24 hours after the last exercise bout. Although elite athletes are not clinically immune deficient, it is possible that the combined effects of small changes in several immune parameters may compromise resistance to common minor illnesses such as upper respiratory tract infection. Protracted immune depression linked with prolonged training may determine susceptibility to infection, particularly at times of major competitions.